Macroeconomic determinants of Malaysia housing price / Nur Nadhirah Ahmad Tajudin - Ahmad Tajudin, Nur Nadhirah (2022)
The purpose of this research is to examine at the factors that affect Malaysian house prices from 2011 to 2021. The continuing rise in Malaysian property prices generates several difficulties, including housing affordability, unsold residential units, and household debt. However, house ownership remains a family dream and is the most expensive investment. The purpose of this research is to look at the link between macroeconomic factors and home prices. Macroeconomic statistics on the exchange rate, GDP growth, loan rate, unemployment rate, real property gain tax, and housing stock were gathered quarterly from 201 1 quarter one to 2021 quarter two. This study also includes descriptive tests. regression analysis (OLS regression), t-tests, f-tests, and heteroscedasticity tests. The purpose of the study shows if dependent variables (HPI) and independent variables such as lending rate, gross domestic product, unemployment rate, exchange rate and real property gain tax have significant relationship or not according 5% of level significant.